2018
DOI: 10.3126/irjms.v3i0.28039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dividend Policy on Share Price of Commercial Bank in Nepal

Abstract: The purpose of this study is to examine the impact of dividend policy on the share price of commercial bank in Nepal. The study is based on pooled cross sectional data of 10 commercial banks. Banks were selected on the basis of their performance on stock market of Nepal, i.e. top gainers and top losers and data are collected from Nepalese commercial banks listed in NEPSE from the F/Y 2012/13 to F/Y 2016/17. The paper investigates the relationship between dividend announcement, EPS, P/E ratio, DPR, on stock pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Pradhan (2003) found a dividend that significantly impacts share price. Baral and Pradhan (2018) discovered that earnings per share, price-earnings ratio, dividend payout ratio, and market price per share were positively and significantly correlated. Joshi (2019) created a shareprice-affecting dividend.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Pradhan (2003) found a dividend that significantly impacts share price. Baral and Pradhan (2018) discovered that earnings per share, price-earnings ratio, dividend payout ratio, and market price per share were positively and significantly correlated. Joshi (2019) created a shareprice-affecting dividend.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Most of the studies (Joshi, 2012;Pradhan, & Dahal, 2016;Baral & Pradhan, 2018) in the past have been limited to studying the impact of financial ratios upon the market share price of commercial banks in Nepal. Life Insurance companies are one of the important sectors in the Nepal Stock Exchange (NEPSE), and factors that influence the market share price of this sector have not yet been studied.…”
Section: S Maskeymentioning
confidence: 99%
“…The research used data from commercial banks and concluded that DPS was the motivating factor in the Nepalese financial sector, and it had influence the market stock price. Baral and Pradhan (2018) examined the relationship of financial indicators like EPS, P/E ratio and dividend payout ratio with the share price. The study was conducted among 10 commercial banks listed in NEPSE.…”
Section: Factors Affecting Market Share Pricementioning
confidence: 99%
“…Using the data of 7 Nepalese commercial banks for the period of 2010 to 2016 Bhattarai found a significant positive impact of dividend on share price. Similarly, Baral and Pradhan (2018) has also analyzed the impact of dividend policy on stock price of Nepalese commercial banks. Baral and Pradhan has selected ten commercial bank listed on Nepal Stock Exchange for the period of 2012/13 to 2016/17.…”
Section: Introductionmentioning
confidence: 99%